Multifactorial determinants of adolescent stunting in West Java, Indonesia: A cross-sectional analysis among students aged 13–15 years - Farera, Gita; Karo, Marni Br; Manullang, Riyen Sari (PT. Mega Science Indonesia, 2024)
Stunting in adolescents remains a significant public health concern, with far-reaching implications for physical and cognitive development that extend into adulthood. This condition, characterized by a height below minus two standard deviations (-2 SD) from the WHO median growth standard, stems from chronic malnutrition and inadequate growth during critical developmental periods. This study aimed to identify factors influencing the incidence of stunting among adolescents aged 13–15 years at SMP Negeri 2 Cikarang Barat in 2022. A descriptive analytical study using a cross-sectional approach was conducted from March to June 2022. This study employed total sampling and recruited 34 adolescents who met the inclusion criteria. Data were collected via validated questionnaires and standardized anthropometric measurements. Statistical analysis included univariate descriptive statistics and bivariate analysis via the chi-square test (α = 0.05). The analysis revealed significant associations between the incidence of stunting and several factors, including nutritional patterns (P = 0.027), birth weight (P = 0.046), birth length (P = 0.048), breastfeeding history (P = 0.048), immunization status (P = 0.050), and family income (P = 0.027). The predominant characteristics of the study population were female sex (67.6%), unfulfilled nutritional patterns (70.6%), low birth weight (64.7%), and short birth length (67.6%). Additionally, 67.6% reported a nonexclusive breastfeeding history, and 70.6% came from low-income families. This study identified multiple significant factors associated with adolescent stunting, emphasizing the complex interplay between early-life factors, nutritional patterns, and socioeconomic conditions. Maternal age at delivery, height, education, and employment status were not significantly associated. These findings suggest a need for comprehensive interventions targeting both nutritional and socioeconomic factors to address adolescent stunting effectively.